Evidence for alteration of the vitamin D-endocrine system in obese subjects. - N H Bell; S Epstein; A Greene; J Shary; M J Oexmann; S Shaw (The Journal of Clinical Investigation, 1985)
Serum immunoreactive parathyroid hormone (PTH) is increased in obese as compared with nonobese subjects and declines with weight loss. To determine whether alteration of the vitamin D-endocrine system occurs in obesity and whether ensuing secondary hyperparathyroidism is associated with a reduction in urinary calcium, a study was performed in 12 obese white individuals, five men and seven women, and 14 nonobese white subjects, eight men and six women, ranging in age from 20 to 35 yr. Body weight averaged 106 +/- 6 kg in the obese and 68 +/- 2 kg in the nonobese subjects (P less than 0.01). Each of them were hospitalized on a metabolic ward and were given a constant daily diet containing 400 mg of calcium and 900 mg of phosphorus. Whereas mean serum calcium, serum ionized calcium, and serum phosphorus were the same in the two groups, mean serum immunoreactive PTH (518 +/- 48 vs. 243 +/- 33 pg/ml, P less than 0.001), mean serum 1,25-dihydroxyvitamin D [1,25(OH)2D] (37 +/- 2 vs. 29 +/- 2, P less than 0.01), and mean serum Gla protein (33 +/- 2 vs. 24 +/- 2 ng/ml, P less than 0.02) were significantly higher, and mean serum 25-hydroxyvitamin D (25-OHD) (8 +/- 1 vs. 20 +/- 2 ng/ml, P less than 0.001) was significantly lower in the obese than in the nonobese men and women. Mean urinary phosphorus was the same in the two groups, whereas mean urinary calcium (115 +/- 10 vs. 166 +/- 13 mg/d, P less than 0.01) was significantly lower, and mean urinary cyclic AMP (3.18 +/- 0.43 vs. 1.84 +/- 0.25 nM/dl GF, P less than 0.01) and creatinine clearance (216 +/- 13 vs. 173 +/- 6 liter/d, P less than 0.01) were significantly higher in the obese than in the nonobese individuals. There was a significant positive correlation between percentage of ideal body weight and urinary cyclic AMP (r = 0.524, P less than 0.01) and between percentage of ideal body weight and serum immunoreactive PTH (r = 0.717, P less than 0.01) in the two groups. The results provide evidence that alteration of the vitamin D-endocrine system in obese subjects is characterized by secondary hyperparathyroidism which is associated with enhanced renal tubular reabsorption of calcium and increased circulating 1,25(OH)2D. The reduction of serum 25-OHD in them is attributed to feedback inhibition of hepatic synthesis of the precursor by the increased serum 1,25(OH)2D.